2021
DOI: 10.4266/acc.2021.00500
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prone position on outcomes of COVID-19 patients with spontaneous breathing

Abstract: Background: In this study, we explored whether early application of the prone position (PP) can improve severe hypoxemia and respiratory failure in coronavirus disease 2019 (COVID-19) patients with spontaneous breathing.Methods: This is a prospective observational study of severe, critically ill adult COVID-19 patients admitted to the intensive care unit. All vital parameters were recorded in real time for all patients. Moreover, the results of chest computed tomography (CT), when available, were analyzed.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…A group of Tunisian investigators recently explored whether the early application of prone positioning can improve severe hypoxemia and respiratory failure in coronavirus disease 2019 (COVID-19) patients with spontaneous breathing—through a prospective observational study of patients admitted to the intensive care unit (ICU). After studying 21 subject-patients and 17 control-patients, who underwent prone positioning within 6 hours following ICU admission, they reported affirmatively in Acute and Critical Care [ 1 ] that yes, early prone positioning can improve severe hypoxemia—and significantly so.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A group of Tunisian investigators recently explored whether the early application of prone positioning can improve severe hypoxemia and respiratory failure in coronavirus disease 2019 (COVID-19) patients with spontaneous breathing—through a prospective observational study of patients admitted to the intensive care unit (ICU). After studying 21 subject-patients and 17 control-patients, who underwent prone positioning within 6 hours following ICU admission, they reported affirmatively in Acute and Critical Care [ 1 ] that yes, early prone positioning can improve severe hypoxemia—and significantly so.…”
mentioning
confidence: 99%
“…In the article, “Impact of prone position on outcomes of COVID-19 patients with spontaneous breathing” [ 1 ] all of 21 subject-patients were placed in prone position for 2 to 4 hours (as tolerated by the patient) followed by 2 hours of supine positioning during the day, and placed in prone position at night, when possible. 2022-02-14“Gravitational ischemia in the brain” results from the mass effect of one part of the brain upon another in a gravitational field [ 2 , 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
In an observational study of patients admitted to the intensive care unit (ICU) [1], we showed that early application of prone positioning can improve severe hypoxemia and respiratory failure in coronavirus disease 2019 (COVID-19) patients with spontaneous breathing. In that study [1], we included 21 patients who underwent prone positioning within 6 hours following ICU admission and 17 control patients, and we concluded that early prone positioning can significantly improve severe hypoxemia. This improvement was not, however, associated with a reduction in the mortality rate or in the use of invasive mechanical ventilation (P>0.05 for both).
…”
mentioning
confidence: 99%
“…The authors suggest that intermittently elevating the patient's head by 30° may be helpful, as it may decrease intra-cranial pressure, prevent neurological complications, and improve the outcomes of these patients. Although we agree with Jaster and Ottaviani's [3] hypothesis that gravitational consequences in the brain may contribute to delirium in the ICU in patients requiring sedation and invasive mechanical ventilation, we think that, for several reasons, this hypothesis cannot be applied in non-intubated patients with acute respiratory distress syndrome (ARDS) due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.First, unlike severe patients requiring sedation and mechanical ventilation, the position of patients with spontaneous breathing is usually changed from supine to prone frequently (every 2 to 4 hours), as described in most published studies [1,2], and according to Jaster and Ottaviani [3], doing so can prevent brain ischemia because it is reversible in its early stages.…”
mentioning
confidence: 99%